THE INTERSECTION OF LAW AND ECONOMICS IN A SOCIAL CONTEXT: A REVIEW OF RECENT LITERATURE - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This literature review explores the intersection between law and economics in a social context, focusing on the dynamics and interplay between the two fields. The study found that a strong and fair legal system is an essential prerequisite for efficient economic operations, creating certainty, protecting property rights, and resolving disputes effectively. In addition, proper regulation of the law can foster innovation and sustainable economic growth. On the other hand, changes in the structure of the economy, such as globalisation and technological development, demand adaptations in legal regulation to face new challenges. In addition, law plays a crucial role in reducing socio-economic inequality through specialised legislation and wealth redistribution policies, which aim to create social stability and justice. In conclusion, the interaction of law and economy requires an inclusive and adaptive approach to ensure sustainable and equitable economic development, taking into account changing social needs.